Business Students’ Attitude to Social Responsibility - Barizsné Hadházi, Edit; Ujhelyi, Mária; Kiss, Zsuzsanna (International Journal of Engineering and Management Sciences, 2018)
The companies’ most important goal is the satisfaction of consumers’ needs and the profitmaking. But nowadays the companies have to deal with the activity of corporate social responsibility, too. Therefore it can be interesting to research about the next questions: can ethics be taught? Do we have to teach ethics in the schools and especially in the business schools? What are the students’ attitudes toward the social responsibility? Are students sensitive and open-minded connection with this issues? The aims of the study were to examine responsible management attitudes among business students at the University of Debrecen (Faculty of Economics and Business). We draw their CSR pyramid (based on Carroll model) and present their opinion in reference to business education’s role in social issues.